The correlation between knowledge level of maxillary anatomical structures and panoramic radiograph interpretation among preclinical dentistry students at Mulawarman University - Balqis, Salsabila Nazwa; Agustin, Sylvia; Munir, Musnar; Rokhim, Saiful; Danial, Danial (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2025)
Objectives: This study aimed to find out the correlation between the knowledge level of maxillary anatomical structures and the interpretation of panoramic radiographs among preclinical dentistry students at the University of Mulawarman. Materials and Methods: This quantitative research utilized a cross-sectional design. The employed sample technique was non-probability total sampling, focusing on preclinical dentistry students from the 2021–2022 academic year who had finished courses in panoramic radiograph interpretation. The data collection included two validated questionnaires: one measuring knowledge of maxillary anatomical components and the other testing the ability to interpret panoramic radiographs. The Spearman correlation test was employed for data analysis. Results: The findings revealed that 60.7% of students were classified as possessing a limited understanding of maxillary anatomical components, 73.8% had inadequate skills in reading panoramic radiographs, and 54.1% showed poor performance in both domains. The correlation test indicated a significant association between knowledge of maxillary anatomical structures and the interpretation of panoramic radiographs, with a Sig. (2-tailed) value of less than 0.001. Conclusion: A significant correlation exists between the knowledge level of maxillary anatomical structures and the interpretation of panoramic radiographs among preclinical dentistry students at Mulawarman University. Keywords: Knowledge level, maxillary anatomical structures, interpretation, panoramic radiography, preclinical students